2006
DOI: 10.1002/med.20054
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 integrase inhibitors: 2003–2004 update

Abstract: The integration of viral cDNA into the host genome is an essential step in the HIV-1-life cycle and is mediated by the virally encoded enzyme, integrase (IN). Inhibition of this process provides an attractive strategy for antiviral drug design. The discovery of beta-diketo acid inhibitors played a major role in validating IN as a legitimate antiretroviral drug target. Over a decade of research, a plethora of IN inhibitors have been discovered and some showed antiviral activity consistent with their effect on I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 92 publications
0
42
0
Order By: Relevance
“…Compounds incorporating a β-ketoenol moiety have yielded clinical integrase inhibitor drug candidates [1]. Tomassini et al reported a series of β-ketoenol derivatives as e ective inhibitors drug of in uenza viral replication in both in vitro cell culture replication assays and in vivo mouse challenge model, without exhibiting any cytotoxicity [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds incorporating a β-ketoenol moiety have yielded clinical integrase inhibitor drug candidates [1]. Tomassini et al reported a series of β-ketoenol derivatives as e ective inhibitors drug of in uenza viral replication in both in vitro cell culture replication assays and in vivo mouse challenge model, without exhibiting any cytotoxicity [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]). Using this in vitro method we present here the activity of six small molecule IN inhibitors from five different structural classes tested against wild type (WT) IN, a soluble double mutant (F185K/ C280S) protein (SM), and two other IN mutants containing an additional substitution at position C130 (Ala and Ser).…”
Section: Introductionmentioning
confidence: 99%
“…Many integrase inhibitors have been discovered during the past 10 years, with two of them presently in clinical trials (for review, see Pommier et al, 2005;Dayam et al, 2006;DeJesus et al, 2006;Semenova et al, 2006b). The binding sites of only two inhibitors, 5CITEP and Y-3, have been determined by X-ray crystallography (Lubkowski et al, 1998;Goldgur et al, 1999).…”
mentioning
confidence: 99%